2016
DOI: 10.1002/bjs.10229
|View full text |Cite
|
Sign up to set email alerts
|

Cohort study of mesenteric panniculitis and its relationship to malignancy

Abstract: MP does not behave like a paraneoplastic phenomenon. The association with malignancy is most likely an epiphenomenon of the many CT images acquired for staging of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…Lymphoma was the most common malignancy followed by prostate, melanoma, lung and renal cell cancer. 18,19 Furthermore; studies have shown association of SM with conditions like sclerosing cholangitis, Riedel thyroiditis, mixed connective tissue disease, ankylosing spondylitis, Sjogren's syndrome tuberculosis, acute pancreatitis and granulomatous diseases. 1,13,20 Only significant finding in our patient was partially incarcerated hernia.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoma was the most common malignancy followed by prostate, melanoma, lung and renal cell cancer. 18,19 Furthermore; studies have shown association of SM with conditions like sclerosing cholangitis, Riedel thyroiditis, mixed connective tissue disease, ankylosing spondylitis, Sjogren's syndrome tuberculosis, acute pancreatitis and granulomatous diseases. 1,13,20 Only significant finding in our patient was partially incarcerated hernia.…”
Section: Discussionmentioning
confidence: 99%
“…Malignancy was identified in 45 patients (38%) (34 males). The most common malignancies were colorectal (14), lymphoma (13), and urogenital tract (7). Malignancies were diagnosed after the detection of mesenteric panniculitis in 13 patients.…”
Section: Khasminsky Et Al [11] 28712750mentioning
confidence: 99%
“…The imaging findings of MP are not specific and reflect the existence of an inflammatory process of the mesenterium that occurs both on inflammation and tumorous pathologies. [2][3][4][5][6][7] Moreover, MP has also been reported in association with systemic vasculitis such as Henoch-Schönlein purpura. 9 The imaging findings to the diagnosis of MP is based on typical CT features that include a mass effect of neighbouring gastrointestinal structures, a mesenteric slightly heterogenous well-circumscribed fatty proliferation surrounded by a peripheral capsule and internal small soft tissue nodules surrounded by a hypoattenuating halo.…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…[1][2][3][4] Definitive treatment for MP is still controversial in the medical literature with both medical and surgical approaches referred. For medical treatment, prednisolone, azathioprine, tamoxifen, thalidomide, antibiotics, infliximab and cyclophosphamide have been studied as acceptable options.…”
Section: Rare Diseasementioning
confidence: 99%
See 1 more Smart Citation